Reframing female leadership through accommodation strategies: A feminist stylistic lens on public speaking - Talib, Hawraa Muhammad; Mubarak, Ahmed Sahib (Edelweiss Applied Science and Technology, 2025)
Feminist leaders often adopt unique language styles tailored to connect with or distance themselves from their audiences. This study seeks to explore these stylistic variations using feminist stylistics, focusing on how accommodation is achieved through two strategies: convergence and divergence. Analyzing six public speeches by by Hooks [1] and Obama [2] the research identifies 21 convergence and 19 divergence feminist stylistic devices (FSDs) operating at phonological, semantic, and syntactic levels. These devices illustrate how language adapts to draw closer to or distance itself from listeners. To the best of the researcher’s knowledge, the application of feminist stylistics to analyze accommodation strategies in public speeches by female leaders has not been previously studied, highlighting a gap that this research aims to address. The study applies Feminist Stylistics and Communication Accommodation Theory (CAT) to analyze convergence and divergence strategies in six public speeches The Theoretical Framework is based on multiple theories including Giles [3] Communication Accommodation Theory Mills [4] Mills’ Feminist-Stylistic theory, Galperin [5] stylistic theory, Palmer [6] theory on mood and modality, Jeffries [7] Critical Stylistic theory Filimonova’s theory of Filimonova [8] as well as Burke [9] theory of Identification in Rajan [10].